Brilliance and fire : a biography of diamonds - Bergstein, Rachelle (Harper, 2016)
"Sheds new light on the enticing, often surprising, story of our society's enduring obsession with the hardest gemstone, offering a fascinating history of its origins and revealing its greatest champions and most colorful enthusiasts. 25,000 first printing,"--NoveList.